Estabilidade de frequência e controle automático de geração: projeto de controlador ótimo LQR aplicado à geração termoelétrica considerando sistemas elétricos interligados - Moraes, Conrado Gabriel Sodre Alves de (2020)
The constant growth in energy demand, linked to economic and industrial development, brings with it the inherent need for expansion of the Electric Power System (EPS), as well as its means of generation, capable of supplying the energy deficit created by the dizzying increase in EPS loads. This allows for the emergence of recurring problems such as the instability of the electrical frequency that compromises the continuity of the energy supply and the quality of the energy provided to the final consumer. This work’s main objective is to develop a design and simulation methodology based on optimal control techniques via LQR, together with its application in EPS through the modeling of the dynamic elements of the frequency stability control system, also known as Automatic Generation Control (AGC). In addition, different design scenarios of LQR controllers will be computationally analyzed through simulations, analyzing the response of the main system control variables from the perspective of EPS stability, and showing the performance of the controllers involved in the simulations. The simulations developed in this work consider the application of instability events in the system in the form of sudden load growths, considering a multi-machine control loop model system with steam thermal turbines, composed of two control areas interconnected through a transmission line. For the simulations, the MATLAB software, through which the LQR controller design script is developed will be used in combination with the softwares, SIMULINK and ANATEM, where the frequency control models are built, using block diagram techniques, and the subsequent simulations are developed considering different control scenarios on EPS.